MODEL EVALUASI PENDIDIKAN BERBASIS CIPP PADA SEKOLAH DASAR UNGGULAN: KAJIAN KUALITATIF DI SD MUHAMMADIYAH PLUS SEMARANG - Irianti, Indah Susi; Wahyu Haspri Nur Taryanti; Iim Fathimah; Suranto; Sumardi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study evaluates the effectiveness of the educational system at SD Muhammadiyah Plus Semarang using the Context, Input, Process, and Product (CIPP) framework. Positioned as a quality control instrument, this assessment responds to demands for continuous improvement in educational services. Employing a qualitative approach with a case study design, data were gathered through in-depth interviews, direct observation, and document analysis. Six key informants were involved: the principal, vice principal, classroom teachers, program coordinators, and school committee members. Data analysis followed the stages of condensation, presentation, and conclusion drawing, with source triangulation ensuring validity and reliability. The findings indicate that the context component exhibits high alignment between strategic programs, student needs, community expectations, and the institutional vision. In the input dimension, the school benefits from competent teaching staff, adequate infrastructure, and the successful integration of the Merdeka Curriculum with Muhammadiyah values. Structurally, process evaluation shows that instructional activities adopt student-centered approaches, supported by periodic academic supervision and consistent management of flagship programs. Meanwhile, the product dimension confirms an increase in academic and non-academic achievements, robust student character development, and high parental satisfaction. From a macro perspective, the study affirms that educational success is determined by reciprocal relationships between contextual appropriateness, resource maturity, implementation efficiency, and outcomes. Ultimately, this research reinforces the CIPP model as a viable instrument for assessing school quality and serves as a strategic reference for policymakers aiming to enhance basic education continuously.